Exploring Alternative Splicing in Response to Salinity: A Tissue-Level Comparative Analysis Using Arabidopsis thaliana Public Transcriptomic Data - Jesús Hernández-Urrieta; José Miguel Álvarez; José Antonio O’Brien (Plants)
Increased soil salinity is a major threat to global agriculture and food security, caused mainly by anthropogenic activities and changing climatic cycles. Plants responses to salinity involve multiple regulatory layers, from transcriptome reprogramming to proteomic and metabolomic changes. Alternative splicing (AS) plays a role in coordinating the response to salinity, yet its extent, tissue, and condition specificity, remain poorly understood aspects. In this study, we used 52 publicly available RNA-seq datasets of salinity treatment to identify differential alternative splicing (DAS) events and genes participating in the response to this stimulus. Our findings reveal that either independently or coordinately, AS can regulate up to 20% of the transcriptome detected in Arabidopsis, with treatment intensity being the most determining factor. Moreover, we show that AS regulation was highly tissue-specific, with roots displaying strong AS-mediated stress responses. Furthermore, cross-stress comparisons showed that roots have a core set of AS-regulated genes associated with stress response and development, with functionally distinct sets of genes when comparing salt with other stresses, while also conserving a relevant condition-specific response. We demonstrate the need to integrate AS analysis to better understand plant adaptation mechanisms and highlight the key role of AS in salinity responses, revealing shared AS regulation between salt, heat, and drought responses.